Effects of Problem-Based Learning with Educational Games on Mathematical Problem-Solving Across Mathematical Anxiety Levels - Kurnia Amalia; Samsul Maarif (IndoMath: Indonesia Mathematics Education, 2026)
This study examines the impact of Problem-Based Learning (PBL) integrated with the Wordwall edugame on students’ mathematical problem-solving ability in trigonometry ratios based on their anxiety level. A quantitative quasi-experimental design was utilized with a pretest-posttest non-equivalent control group design involving 64 tenth-grade students in Jakarta. The experimental group underwent PBL integrated with Wordwall, while the control group received conventional treatment. Data were gathered through a mathematical problem-solving essay test grounded on Polya’s indicators and an anxiety questionnaire. The findings revealed that the experimental group attained a moderate N-Gain score (M = 0.53), whereas the control group demonstrated a smaller gain (M = 0.15). Statistical analysis indicated a statistically significant difference between the two groups (p < 0.001). Nevertheless, no significant differences were observed across anxiety levels or the interaction effect between treatment and anxiety level. These results suggest that PBL integrated with the Wordwall edugame consistently and effectively enhances students’ mathematical problem-solving ability across all anxiety levels.